2019
DOI: 10.1177/0735633119830764
|View full text |Cite
|
Sign up to set email alerts
|

Automated Writing Evaluation and Feedback: Multiple Metrics of Efficacy

Abstract: The present study extended research on the effectiveness of automated writing evaluation (AWE) systems. Sixth graders were randomly assigned by classroom to an AWE condition that used Project Essay Grade Writing ( n = 56) or a word-processing condition that used Google Docs ( n = 58). Effectiveness was evaluated using multiple metrics: writing self-efficacy, holistic writing quality, performance on a state English language arts test, and teachers' perceptions of AWE's social validity. Path analyses showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 68 publications
(106 reference statements)
2
69
0
Order By: Relevance
“…Automated support for revision feedback using analytic rubrics has been applied to second language learners' persuasive essays [40], college students' physics lab reports [41], and middle school students in English language arts (ELA) classes [42]. Liu et al [40] developed machine-learned models by training on pairs of student sentences and teacher comments from a previously collected dataset of L2 learner essays.…”
Section: Technology For Experiential Learning a Previous Work Omentioning
confidence: 99%
See 2 more Smart Citations
“…Automated support for revision feedback using analytic rubrics has been applied to second language learners' persuasive essays [40], college students' physics lab reports [41], and middle school students in English language arts (ELA) classes [42]. Liu et al [40] developed machine-learned models by training on pairs of student sentences and teacher comments from a previously collected dataset of L2 learner essays.…”
Section: Technology For Experiential Learning a Previous Work Omentioning
confidence: 99%
“…Results indicated that teachers gave more feedback on higher-level writing skills to students in the combined condition, and that reliance on PEG saved one-third to half the time it took to provide feedback without PEG. In a somewhat larger study, middle school students in ELA classes using PEG had more positive writing self-efficacy and higher scores on the state ELA test than a control group [42]. Other machine learning methods for predicting scores using all or some of the analytic rubric dimensions have also been investigated for college level L2 essays [45] and middle school argument writing [46].…”
Section: Technology For Experiential Learning a Previous Work Omentioning
confidence: 99%
See 1 more Smart Citation
“…10 This is perhaps surprising, considering 7 In particular, we are not aware of any impact evaluation that does so in a post-primary education context. Outside post-primary education, Shermis et al (2008), Palermo and Thomson (2018) and Wilson and Roscoe (2019) use experimental data on grades 6-10. However, we believe there are important limitations in the results presented in these papers.…”
Section: Introductionmentioning
confidence: 99%
“…Most outcomes in this literature are also not economically important. Wilson and Roscoe (2019) present an evaluation of the effects Project Essay Grade Writing in Texas on the state English Language Arts test but treatment was randomized using a small sample of clusters (3 teachers in 10 different classrooms) and the control group received a recommendation of using Google Docs as an alternative resource.…”
Section: Introductionmentioning
confidence: 99%